Lower limb muscle coactivation levels in healthy younger and older adults during functional dual-task gait - Hallal, Camilla Zamfolini [UNESP]; Marques, Nise Ribeiro [UNESP]; Vieira, Edgar Ramos; Brunt, Denis; Spinoso, Deborah Hebling [UNESP]; Castro, Alex [UNESP]; Cardozo, Adalgiso Coscrato [UNESP]; Goncalves, Mauro [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
The purpose of this study was to investigate the influence of daily cognitive task on stiffness of old and young female adults during the gait. The study included 17 physically active younger and 18 older women, with low risk of falls. The volunteers were asked to walk on the treadmill at two different gait conditions: normal gait and functional dual-task gait. The electromyographic signals were collected of the lower limb muscles. The percentage of coactivation for the tibialis anterior/gastrocnemius lateralis and tibialis anterior/soleus were significantly higher in elderly than in younger in the normal gait and dual-task gait. Our results suggest that the elderly have a greater stiffness in the ankle joint during gait normal and daily dual task gait. Thus, we conclude that challenging cognitively situations during the gait may increase the risk of falls in this population.

O objetivo deste estudo foi investigar a influência de uma tarefa cognitiva cotidiana sobre a coativação muscular de mulheres idosas e jovens durante a marcha. Participaram do estudo 17 mulheres jovens fisicamente ativas e 18 mulheres idosas com baixo risco de quedas. Os voluntários foram orientados a caminhar sobre uma esteira em duas diferentes condições de marcha: marcha normal e marcha com dupla-tarefa cotidiana. Os sinais eletromiográficos foram coletados dos músculos dos membros inferiores. A porcentagem de coativação para tibial anterior/gastrocnêmio lateral e tibial anterior/sóleo foram significativamente maiores em idosos do que em jovens na marcha normal e marcha com dupla-tarefa. Nossos resultados sugerem que os idosos tem maior coativação muscular no tornozelo durante a marcha normal e marcha com dupla tarefa cotidiana. Assim, nós concluimos que situações cognitivamente desafiadoras durante a marcha podem aumentar o risco de quedas em idosos.
Coativação muscular dos membros inferiores de jovens e idosas saudáveis durante marcha com dupla tarefa funcional
Coactivación muscular del miembro inferior de jóvenes y ancianos saludables durante la marcha con doble tarea funcional
Keywords: elderly; gait; coactivation; falls